Matting films prepared from waterborne acrylic/micro‐SiO2 blends. Issue 13 (11th December 2014) - Ou, Juhua; Zhang, Min; Liu, Hailu; Zhang, Lei; Pang, Hao
ABSTRACT Acrylic resin/micro‐SiO2/polymethyl urea (AC/SiO2/PMU) composites were prepared by physical blends of acrylic resin latex (AC), polymethyl urea resin (PMU), and modified SiO2. The effects of SiO2 and PMU content in the hybrid composites morphology and physical properties were investigated in detail using transmission electron microscopy (TEM), UV‐Vis spectrometry (UV‐Vis), scanning electron microscope (SEM), thermogravimetric analysis (TGA), and contact angle measurement. The results showed that introduction of SiO2 into AC composites could increase the viscosity which caused by gelation and agglomeration of SiO2. The TEM, SEM images, and TGA results indicated that hybrid membranes have phase separation. During the film formation process, a high number of PMU and SiO2 particles of an appropriate size were stranded on the surface of the film to form matting surface. These results highlight the sensitivity of the gloss to the polymer morphology and surface. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41707.